2000
DOI: 10.1002/(sici)1097-4628(20000606)76:10<1602::aid-app16>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the prepolymerization on the properties of thermoplastic polyurethane elastomers. Part II. Relationship between the prepolymer and polyurethane properties

Abstract: The synthesis of thermoplastic polyurethane elastomers (TPUs) is generally carried out using the prepolymer method. To study the influence that the properties of the prepolymer may have in the final TPUs, four TPUs were prepared by using different NCO/OH ratios. The prepolymers and the macroglycol used in their synthesis were characterized in the first part of this article. TPUs were characterized by using gel permeation chromatography, strain-stress measurements, differential scanning calorimetry, and contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…The elastomers analyzed in the current study were synthesized via two different reaction schemes (Fig. 2) in order to ascertain whether the method of synthesis could appreciably influence the elastomer morphology and properties 12–14. The first of these is essentially identical to the procedure used previously, in that all of the polyols (PPG, TPG, PTMEG) are mixed together first and then end capped with MDI.…”
Section: Introductionmentioning
confidence: 99%
“…The elastomers analyzed in the current study were synthesized via two different reaction schemes (Fig. 2) in order to ascertain whether the method of synthesis could appreciably influence the elastomer morphology and properties 12–14. The first of these is essentially identical to the procedure used previously, in that all of the polyols (PPG, TPG, PTMEG) are mixed together first and then end capped with MDI.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the use of this kind of materials able to form hydrogen-bonds result in less direct interactions between phases, causing a higher phase separation. Furthermore, the interactions between silanol and carbonyl groups are weaker than those between NH and ester carbonyl groups, then silica addition increases the polyester chain mobility and, it allows to become more ordered in relation to the TPU without silica (Sánchez-Adsuar et al, 2000;Tien et al, 2001;Nunes et al, 2000;Nunes et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…In this article, we investigate a new route to prepare fabric/activated carbon composites using a thermoplastic polyurethane as composite binder. The polymer choice was due, on one hand, to its good adhesion and mechanical properties and, on the other, to its versatile and controllable properties, depending on its composition and synthesis conditions 9–11…”
Section: Introductionmentioning
confidence: 99%